2017
DOI: 10.1186/s12967-017-1371-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine signatures in chronic fatigue syndrome patients: a Case Control Study and the effect of anakinra treatment

Abstract: BackgroundCytokine disturbances have been suggested to be associated with the Chronic Fatigue Syndrome/Myalgic encephalomyelitis (CFS/ME) for decades.MethodsFifty female CFS patients were included in a study on the effect of the interleukin-1-receptor antagonist anakinra or placebo during 4 weeks. EDTA plasma was collected from patients before and directly after treatment. At baseline, plasma samples were collected at the same time from 48 healthy, age-matched female neighborhood controls. A panel of 92 inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
0
16
1
Order By: Relevance
“…This was also the case for IL-1β when comparing QFS patients with CFS patients and asymptomatic Q fever seropositive controls, and TNFα when comparing QFS patients with CFS patients and healthy controls. Interestingly, circulating IL-6 was also significantly increased in QFS patients compared to healthy controls, an observation that was made before in CFS patients [13, 34]. Looking at the transcriptomes of circulating monocytes in QFS and CFS patients, compared to healthy controls, no genes associated with the IL-6 production pathway seem to be overly expressed.…”
Section: Discussionmentioning
confidence: 60%
“…This was also the case for IL-1β when comparing QFS patients with CFS patients and asymptomatic Q fever seropositive controls, and TNFα when comparing QFS patients with CFS patients and healthy controls. Interestingly, circulating IL-6 was also significantly increased in QFS patients compared to healthy controls, an observation that was made before in CFS patients [13, 34]. Looking at the transcriptomes of circulating monocytes in QFS and CFS patients, compared to healthy controls, no genes associated with the IL-6 production pathway seem to be overly expressed.…”
Section: Discussionmentioning
confidence: 60%
“…Montoya et al (2017) examined 17 cytokines/chemokines, including CCL-11, and found a general elevation in pro-inflammatory cytokine/chemokine levels in CFS patients as compared to controls and, additionally, that these biomarkers were associated with the severity of CFS. Roerink et al (2017) found that MCP-1 and CCL-11 were among the chemokines that were associated with CFS.…”
Section: Discussionmentioning
confidence: 98%
“…IL-10 is produced by monocytes, macrophages, Tregs and Th2-polarised T cells in a state of endotoxin tolerance, and suppresses the CD8 T and CD4 Th1 type cell response making an indispensable contribution to the development of an anti-inflammatory environment (Jiang and Chess 2006 ; Littman and Rudensky 2010 ). The indispensable contribution of IL-10 to the development of endotoxin tolerance (Liu et al 2011b ; Quinn et al 2012 ) is of importance from the perspective of this paper as the upregulation of this cytokine is a common observation in CFS patients (Roerink et al 2017 ; Wong et al 2015 ).…”
Section: Iandons and The Development Of Endotoxin Tolerance Via Ido Uprmentioning
confidence: 98%